Psychiatric Disorders and TRP Channels: Focus on Psychotropic Drugs - Nazıroglu, Mustafa; Demirdas, Arif (Current Neuropharmacology, 2015)
Psychiatric and neurological disorders are mostly associated with the changes in neural calcium ion signaling pathways required for activity-triggered cellular events. One calcium channel family is the TRP cation channel family, which contains seven subfamilies. Results of recent papers have discovered that calcium ion influx through TRP channels is important. We discuss the latest advances in calcium ion influx through TRP channels in the etiology of psychiatric disorders. Activation of TRPC4, TRPC5, and TRPV1 cation channels in the etiology of psychiatric disorders such as anxiety, fear-associated responses, and depression modulate calcium ion influx. Evidence substantiates that anandamide and its analog (methanandamide) induce an anxiolytic-like effect via CB1 receptors and TRPV1 channels. Intracellular calcium influx induced by oxidative stress has an significant role in the etiology of bipolar disorders (BDs), and studies recently reported the important role of TRP channels such as TRPC3, TRPM2, and TRPV1 in converting oxidant or nitrogen radical signaling to cytosolic calcium ion homeostasis in BDs. The TRPV1 channel also plays a function in morphine tolerance and hyperalgesia. Among psychotropic drugs, amitriptyline and capsazepine seem to have protective effects on psychiatric disorders via the TRP channels. Some drugs such as cocaine and methamphetamine also seem to have an important role in alcohol addiction and substance abuse via activation of the TRPV1 channel. Thus, we explore the relationships between the etiology of psychiatric disorders and TRP channel-regulated mechanisms. Investigation of the TRP channels in psychiatric disorders holds the promise of the development of new drug treatments.
Keywords: anxiety